Green tea drinking and multigenetic index on the risk of stomach cancer in a Chinese population - Mu, Li‐Na; Lu, Qing‐Yi; Yu, Shun‐Zhang; Jiang, Qing‐Wu; Cao, Wei; You, Nai‐Chieh; Setiawan, Veronica Wendy; Zhou, Xue‐Fu; Ding, Bao‐Guo; Wang, Ru‐Hong; Zhao, Jinkou; Cai, Lin; et al. (International journal of cancer, 2005)
The purpose of our study was to examine the roles of green tea drinking, other risk and protective factors, and polymorphism of susceptibility genes such as GSTM1, GSTT1, GSTP1, and p53 codon 72 and their possible joint effects on the risk of stomach cancer. A population‐based case‐control study was conducted in Taixing, China, including 206 newly diagnosed cases with stomach cancer and 415 healthy control subjects. Epidemiological data were collected by in‐person interviews using a standard questionnaire. Polymorphisms of susceptibility genes were assayed by PCR‐RFLP techniques. A multigenetic index was created by summing up the number of risk genotypes. The data were analyzed using the logistic regression model. A reverse association between green tea drinking and risk of stomach cancer was observed with an adjusted odds ratio (OR) of 0.59 (95% confidence interval [CI] = 0.34–1.01). Dose‐response relationship was shown (p‐trend < 0.05). A higher score on the multigenetic index was associated with increased risk of stomach cancer with an adjusted OR of 2.21 (95% CI = 1.02–4.79) for those with at least 3 risk genotypes compared to those with <2 risk genotypes. Green tea drinking was suggested to have more than multiplicative interactions with alcohol consumption with an adjusted OR for interaction of 4.57 (95% CI = 1.62–12.89), and with higher multigenetic index with adjusted OR for interaction of 2.31 (95% CI = 0.88–6.03). The protective effect of green tea drinking was observed on the risk of stomach cancer and the possible effect modification by susceptibility genes was suggested. © 2005 Wiley‐Liss, Inc.